PENGARUH KEPUASAN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA PT ASTRA INTERNATIONAL DAIHATSU – DSO MALALAYANG - Supit, Cafry Geraldy; Pelleng, F A.O; Kalangi, J A.F (JURNAL ADMINISTRASI BISNIS (JAB), 2017)
Abstract. Work productivity can be interpreted as an attitude of employee performance to produce something better / better productive, as evidenced by the high motivation and ability. Increased productivity can be achieved if employees who work feel their job satisfaction. Job satisfaction will help companies generate, maintain, and always hire employees to remain productive. In the absence of job satisfaction, employees tend to be unproductive and will even stop working. This study aims to determine the effect of job satisfaction on employee productivity at PT Astra International Daihatsu-DSO Malalayang. This study uses a simple correlation and regression analysis. Results of simple correlation analysis is R = 0.69, it indicates that if the job satisfaction increases, the labor productivity will go up anyway. The degree of this correlation is categorized as, and after the test turned out to be very significant significance. With a coefficient of determination can be seen that 47.3% productivity factor is determined by factors of job satisfaction and the rest is determined by other factors. by using simple regression analysis research shows that job satisfaction have an effect on employee productivity. Keywords: Job Satisfaction, Work Productivity.